2018
DOI: 10.1093/nar/gky1152
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of 8-oxo-7,8-dihydro-2′-deoxyguanosine reveals accumulation of oxidatively-generated damage at DNA replication origins within transcribed long genes of mammalian cells

Abstract: Abstract8-Oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) is one of the major DNA modifications and a potent pre-mutagenic lesion prone to mispair with 2′-deoxyadenosine (dA). Several thousand residues of 8-oxodG are constitutively generated in the genome of mammalian cells, but their genomic distribution has not yet been fully characterized. Here, by using OxiDIP-Seq, a highly sensitive methodology that uses immuno-precipitation with efficient anti–8-oxodG antibodies combined with high-throughput sequencing, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 75 publications
5
84
0
Order By: Relevance
“…Immunocytochemistry was performed according to the manufacturer’s instructions (Trevigen Inc.). The anti-8-oxo-dG antibodies (mouse monoclonal 15A3) were validated by confocal microscopy ( 16 ) and chromatin immunoprecipitation (ChIP) ( 17 ). The signal was resistant to RNase A and sensitive to DNase I and NAC.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry was performed according to the manufacturer’s instructions (Trevigen Inc.). The anti-8-oxo-dG antibodies (mouse monoclonal 15A3) were validated by confocal microscopy ( 16 ) and chromatin immunoprecipitation (ChIP) ( 17 ). The signal was resistant to RNase A and sensitive to DNase I and NAC.…”
Section: Methodsmentioning
confidence: 99%
“…As one example, OxiDIP-seq used an 8-oxodG antibody for immunoprecipitation followed by high-throughput sequencing in human non-tumorigenic epithelial breast cells and mouse embryonic fibroblasts. 55,56 The sequencing revealed that 8-oxodG sites accumulated in the transcribed regions of long genes and at DNA replication origins, overlapping with gH2AX ChIP-seq signals and double-strand breaks. Furthermore, a strong reduction of 8-oxodG was observed within promoter regions with high GC content in quiescent (G0) cells without DNA replication.…”
Section: Genome-wide Mapping Of 8-oxodgmentioning
confidence: 99%
“…This computational effort led to further insights about the molecular mechanisms underlying the heterogeneity of the local mutation rate and the understanding of why certain regions seem to be more, while others less, prone to oxidation. A full description of this work can be found in [19].…”
Section: Use Casesmentioning
confidence: 99%